Improvvisazione libera radicale - Arena, Leonardo Vittorio (Scenari, 2021)
Jazz improvisation follows very strict rules, as to harmony and modal scales, which do not allow it may be considered a true kind of improvisation. It goes without saying that it is not hinted at the jazz geniuses, who changed such rules and worked through them. It should be emphasized a free, radical kind of improvisation, being absolutely free from harmonic, melodic, and rhythmic patterns, or the reference to one music special genre. A musician will be able to express himself completely, and to give rise to his creativity. The only kind of conditioning, if any, will be related to his instrumental practice and music background.